ANALISIS PENGARUH CSR DIMENTIONS TERHADAP ATTITUDINAL LOYALTY AND BEHAVIORAL LOYALTY YANG DIMEDIASI PRICE FAIRNESS PADA KONSUMEN CARREFOUR SURABAYA - OCTAVIA, STEFY (JURNAL ILMIAH MAHASISWA MANAJEMEN, 2012)
The purpose of this research is identify the impact of CSR dimension (environment, community, employee, and product) towards price fairness and the impact of price fairness towards attitudinal loyalty and behavioral loyalty. Reserach design is causal wth 139 samples. Data analysis technique by Structural Equation Model (SEM) with lisrel program. The result of this research showing that environment and community proved have impact towards price fairness, but employee and product not proved the impact towards price fairness. Price fairness have impact towards attitudinal loyalty and behavioral loyalty.